Prevalence of hospital-acquired infections (HAIs) and associated factors in Ethiopia: a systematic review and meta-analysis protocol - Birhan Gebresillassie Gebregiorgis; Goitom Molalign Takele; Kassahun Dires Ayenew; Yosef Eshetie Amare (BMJ Open)
Introduction Hospital-acquired infections (HAIs) are public health problems of global concern and are notably prevalent in developing countries. The prevalence of HAI and its associated factors are not well described in the context of Ethiopia. Currently, the nationwide prevalence of HAI and its corresponding associated factors have not been formally reported in Ethiopia. This review will provide an estimate of the prevalence of HAI and its associated factors.Methods Scholarly articles will be selected from the Embase, PubMed, Cochrane library, Hinary, Scopus, Web of Science and Google Scholar databases. Articles within the timeline of January 2000 to December 2020 will be included for review. Observational studies, randomised trials, surveys, surveillance reports, published and grey literature that reported the prevalence of HAI or factors associated with HAI reported as OR (95% CI) with no language restriction will be included in the analysis. Screening and selection of articles will be done using web-based Covidence software. The article’s quality and risk of bias will be critically appraised using Johanna Briggs Institute quality appraisal checklist. Random effects model using the inverse variance method will be conducted to estimate the prevalence of HAI. To examine heterogeneity, the Q statistics and I2 statistics will be conducted. Publication bias will be investigated using Begg’s correlation method and Egger’s weighted regression test. All analyses will be performed with STATA (V.14) software.Ethics and dissemination Ethical approval is not required for meta-analysis reviews as participants are not included. The review will be submitted for publication in peer-reviewed journals.